Dreaming of the Day ; Yes, Sir! She's Good and Plenty - Grossbart, Eddie; Noble, Ray; Murray, Alan; Lenton; Metropole Dance Band; Allan Selby & his Band; Metropole
sisällön kuvaus: Sida A: Metropole A Striking Record Recorded Electrically Fox-Trot Vocal Refrain Dreaming of the Day (Grossbart-Noble-Murray) Metropole Dance Band 1724 1152 Made in England by the Metropole Gramophone Co. Ltd.